Résister n'est pas un crime - Collard, Marie-France (Belgium : Le Clea, 2007)
In January 2006, 11 presumed members of a Turkish Marxist organization called DHKP-C and labeled as ‘terrorist’ by the EU, the US and Turkey were tried in Belgium. 7 of them were eventually sentenced to 4 to 7 years of imprisonment, which were later either confirmed or increased by a Court of Appeal. The film traces the steps taken by the Belgian legal system against one of its citizens, namely Bahar Kimyongür, and his DHKP-C comrades. It questions the decision reached by the Court of Cassation in Brussels and discusses the anti-terrorist laws within the European framework of decision-making. It also exposes the consequences of these decisions for social protest movements and for movements defending basic liberties.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films